Delirium associated with concomitant use of duloxetine and bupropion in an elderly patient. Issue 2 (5th April 2016) - Ma, Szu‐Pin; Tsai, Chia‐Jui; Chang, Cheng‐Chen; Hsu, Wen‐Yu
Abstract: Delirium is common in daily practice. Drug‐induced delirium constitutes approximately one‐third of all cases of delirium. In cases characterized by the limited efficacy of a single antidepressant, a combination of two antidepressants is required, which may induce a complex drug–drug interaction. We reviewed a case of duloxetine‐ and bupropion‐related delirium in an elderly male patient in our clinical practice. The patient was diagnosed with major depressive disorder and was treated with duloxetine. However, he developed delirium 10 days after bupropion was added to his treatment regimen. Three days after the cessation of bupropion, his delirious condition gradually improved. Duloxetine and bupropion are both cytochrome P450 2D6 inhibitors that may result in a higher level of hydroxybupropion. An increased level of hydroxybupropion may cause the elevation of dopamine and a risk of subsequent delirium. We should be aware of the risk of delirium induced by drug–drug interactions.